Modified current collector, preparation method thereof and lithium ion battery
By using modified current collectors in lithium-ion batteries and using composite structures of nano-carbon coatings and functionalized modified coatings, the poor performance of lithium-ion batteries caused by low porosity is solved, and the battery's rate performance and cycle are improved life.
Patent Information
- Application Number
- CN202411527251.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-29
AI Technical Summary
The functional coating with lower porosity in existing lithium-ion batteries hinders the diffusion of Li+ in the electrodes, resulting in poor rate performance and cycle life of lithium-ion batteries.
A modified current collector is adopted, which includes a first functional modified coating, a first nanocarbon coating, a current collector, a second nanocarbon coating and a second functional modified coating arranged in sequence, through the nanocarbon The composite of coating materials and functionally modified materials increases porosity, and improves interface contact impedance through the gradient design of electron diffusion channels and improves bonding strength.
It improves the diffusion rate of Li+ in the electrode, increases the ion transmission capacity, reduces the polarization internal resistance, extends the charging and discharge cycle life of lithium-ion batteries, and improves the rate performance and cycle life.
Smart Images

Figure CN119252929A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of current collectors, and in particular to a modified current collector and a preparation method thereof, and a lithium ion battery. Background Art
[0002] With the rapid development of lithium-ion battery technology, higher requirements are now being placed on the power performance, rate performance and cycle life of lithium-ion batteries. Phosphate-based power batteries usually use carbon coating to optimize and modify due to the low electrical conductivity and electronic conductivity of the material structure itself. However, the contact between the current collector and the active material of a lithium-ion battery is also an important factor affecting the charge and discharge performance. Therefore, the modification of the current collector has also become an effective method to improve the performance of lithium-ion batteries. A commonly used modification method is to use a functional coating to treat the surface. For example, dispersed nano-conductive graphite and carbon black particles are evenly coated on aluminum foil or copper foil to prepare a carbon-coated foil, thereby reducing the internal resistance of the battery and reducing polarization, thereby improving the rate performance and cycle life of lithium-ion batteries. However, the functional coating with lower porosity hinders Li + The diffusion rate in the electrode decreases the rate performance and cycle life of the lithium-ion battery. Summary of the invention
[0003] The main purpose of the present invention is to provide a modified current collector and a preparation method thereof, and a lithium ion battery, so as to solve the problem that the functional coating with low porosity in the prior art hinders Li + Diffusion in electrodes leads to poor rate performance and cycle life of lithium-ion batteries.
[0004] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a modified current collector is provided, which comprises a first functional modified coating, a first nano-carbon coating, a current collector, a second nano-carbon coating and a second functional modified coating which are stacked in sequence; the first nano-carbon coating and the second nano-carbon coating each independently comprise a nano-carbon coating material; the first functional modified coating and the second functional modified coating each independently comprise a nano-carbon coating material and a functionalized modified material.
[0005] Furthermore, the bending factor ratio of the modified current collector is in, is the bending factor of the first nano-carbon coating or the second nano-carbon coating, is the bending factor of the first functional modified coating or the second functional modified coating; the bending factor ratio of the modified current collector is 5 to 90%, preferably 10 to 80%; and / or the electronic conductivity ratio of the modified current collector is Among them, δ C is the electronic conductivity of the first nanocarbon coating or the second nanocarbon coating, δ Fis the electronic conductivity of the first functional modified coating or the second functional modified coating; the electronic conductivity ratio of the modified current collector is 2 to 85%, preferably 5 to 80%.
[0006] Furthermore, the mass content of the functionalized modified material in the first functional modified coating is 0.05 to 50%; and / or, the mass content of the functionalized modified material in the second functional modified coating is 0.05 to 50%; and / or, the nanocarbon coating material is selected from any one or more of conductive graphite, carbon black, graphene, carbon nanotubes and VGCF; and / or, the functionalized modified material is selected from any one or more of transition metal oxide nanowires, transition metal oxide nanofibers, conductive polymer nanowires, conductive polymer nanofibers, MXene and MOFs.
[0007] Furthermore, the transition metal oxide nanowires and transition metal oxide nanofibers are each independently selected from RuO 2 、MnO 2 、V 2 O 5 、NiO 2 and any one or more of their corresponding derivatives; and / or, the conductive polymer nanowires and the conductive polymer nanofibers are each independently selected from any one or more of polyaniline, polypyrrole, polythiophene and their corresponding derivatives; and / or, MXene is selected from the group consisting of: n+1 X n T x Two-dimensional layered materials derived from transition metal carbides, with a general chemical formula of M n+1 X n T x The two-dimensional layered material derived from transition metal nitrides, with the general chemical formula M n+1 X n T x Any one or more of the two-dimensional layered materials derived from transition metal carbonitrides, wherein M is a transition metal element, and M is selected from any one or more of Ti, V, Cr, Zr and Nb; X is a carbon element and / or a nitrogen element, T x is a surface group, the surface group is selected from any one or more of hydroxyl, fluorine, and carbonyl, 1≤n≤4; and / or, MOFs is a porous material composed of metal and organic ligands, the metal is metal ions and / or metal clusters, and MOFs is selected from any one or more of mesh metal-organic framework materials, zeolite imidazolate framework materials, Levasil framework materials, and pore-channel framework materials.
[0008] Further, the thickness of the first nano-carbon coating and the second nano-carbon coating is independently 0.5 to 80 μm; and / or, the width of the first nano-carbon coating and the second nano-carbon coating is independently 50 to 1000 mm; and / or, the thickness of the first functional modified coating and the second functional modified coating is independently 0.5 to 80 μm; and / or, the width of the first functional modified coating and the second functional modified coating is independently 50 to 1000 mm; and / or, the first functional modified coating, the first nano-carbon coating, the second nano-carbon coating, the first functional modified coating, the second functional modified ... The thickness ratio of the nano-carbon coating and the current collector is 10-60:10-60:10-15; and / or, the thickness ratio of the second functional modified coating, the second nano-carbon coating and the current collector is 10-60:10-60:10-15; and / or, the thickness of the current collector is 6-16 μm; the current collector is copper foil or aluminum foil; and / or, the thickness of the aluminum foil is 12-16 μm; and / or, the thickness of the copper foil is 6-12 μm; and / or, the porosity of the modified current collector is 20-80%, preferably 40-80%.
[0009] According to another aspect of the present invention, a method for preparing the above-mentioned modified current collector is provided, and the preparation method comprises: step S1, mixing raw materials including nano-carbon coating material, a first dispersant, a first organic solvent and a first adhesive for a first time to obtain a nano-carbon coating slurry; step S2, mixing raw materials including nano-carbon coating material, a functional modified material, a second dispersant, a second organic solvent and a second adhesive for a second time to obtain a functional modified coating slurry; step S3, coating the nano-carbon coating slurry on two opposite surfaces of the current collector respectively to form a first nano-carbon coating and a second nano-carbon coating; step S4, coating the functional modified coating slurry on the surfaces of the first nano-carbon coating and the second nano-carbon coating away from the current collector respectively to form a first functional modified coating and a second functional modified coating, so as to obtain a modified current collector.
[0010] Further, the above step S1 also includes: step S11, performing a first dispersion of the nano-carbon coating material, the first dispersant and the first organic solvent to obtain a first conductive paste; step S12, performing a first mixing of the first conductive paste and the first adhesive to obtain a nano-carbon coating slurry; wherein the mass ratio of the nano-carbon coating material, the first dispersant and the first organic solvent is 1:0.01-0.5:2-50; and / or, the viscosity of the nano-carbon coating slurry is 800-10000 mPa·s, preferably 850-9000 mPa·s; and / or, the speed of the first dispersion The speed is 20 to 10000 rpm, and / or the first dispersion time is 0.5 to 1.5 h, and / or the first mixing time is 0.5 to 24 h; and / or the first dispersant is selected from any one or more of anionic dispersants, cationic dispersants, nonionic dispersants and electrically neutral dispersants; and / or the first organic solvent is selected from any one or more of N-methylpyrrolidone, γ-butyrolactone, and dimethylformamide; and / or the first adhesive is selected from any one or more of polyvinylidene fluoride, styrene-butadiene rubber, carboxymethyl cellulose, polyacrylic acid, and polyacrylonitrile.
[0011] Further, the above step S2 also includes: step S21, performing a second dispersion of the nano-carbon coating material, the functional modified material, the second dispersant and the second organic solvent to obtain a second conductive paste; step S22, performing a second mixing of the second conductive paste and the second adhesive to obtain a functional modified coating slurry; wherein the mass ratio of the nano-carbon coating material, the functional modified material, the second dispersant and the second organic solvent is 1: 0.01-0.95: 0.01-0.5: 2-50; and / or the viscosity of the functional modified coating slurry is 1200-10000 mPa·s, preferably 1500-9500 mP·s. a·s; and / or, the rotation speed of the second dispersion is 50 to 8000 rpm, and / or, the time of the second dispersion is 0.5 to 1.5 h, and / or, the time of the second mixing is 0.5 to 24 h; and / or, the second dispersant is selected from any one or more of anionic dispersants, cationic dispersants, non-ionic dispersants and electrically neutral dispersants; and / or, the second organic solvent is selected from any one or more of N-methylpyrrolidone, γ-butyrolactone, and dimethylformamide; and / or, the second adhesive is selected from any one or more of polyvinylidene fluoride, styrene-butadiene rubber, carboxymethyl cellulose, polyacrylic acid, and polyacrylonitrile.
[0012] Furthermore, the above-mentioned step S3 also includes cleaning the current collector before coating, and the cleaning agent used for the cleaning treatment is an acid solution, and the acid solution is selected from any one or more of 0.5-50wt% acetic acid solution, 0.5-37wt% hydrochloric acid solution and 0.5-45wt% phosphoric acid solution; and / or the pH value of the acid solution is 1-6.
[0013] According to another aspect of the present invention, a lithium-ion battery is provided, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet and / or the negative electrode sheet comprises the above-mentioned modified current collector.
[0014] By applying the technical solution of the present invention and adopting the modified current collector of the above stacked structure of the present application, on the one hand, the first nano-carbon coating and the second nano-carbon coating can enhance the conductive network between the active material and the current collector; on the other hand, the nano-carbon coating material and the functionalized modified material in the first functional modified coating and the second functional modified coating are compounded to increase the porosity, thereby further improving the Li + The diffusion rate in the electrode increases the Li + The transmission capacity of ions, and the electron diffusion channel formed from the first nanocarbon coating to the first functional modified coating (or from the second nanocarbon coating to the second functional modified coating) is designed with an increasing gradient, thereby improving the interface contact impedance and the bonding strength, thereby alleviating the performance degradation caused by the interface stress during the long cycle. Through the synergistic effect of the above two aspects, it is possible to enhance the conductive network between the active material and the current collector, and at the same time increase the ion transmission capacity, thereby reducing the polarization internal resistance and inhibiting the growth of the DCR of the lithium-ion battery during the charge and discharge cycle, thereby improving the rate performance and cycle life of the lithium-ion battery. In addition, the modified current collector having the above structure has abundant porosity, which helps to improve its wettability in the electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0016] Figure 1 The schematic diagram of the structure of the modified current collector of the present application is shown;
[0017] Among them, the above drawings include the following reference numerals:
[0018] 1. First functional modified coating; 2. First nanocarbon coating; 3. Current collector; 4. Second nanocarbon coating; 5. Second functional modified coating; 6. Nanocarbon coating material; 7. Transition metal oxide nanowires and transition metal oxide nanofibers; 8. Conductive polymer nanowires and conductive polymer nanofibers; 9. MXene; 10. MOFs. DETAILED DESCRIPTION
[0019] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0020] As analyzed in the background of this application, the prior art has a functional coating with low porosity that hinders Li + Diffusion in the electrode leads to poor rate performance and cycle life of lithium-ion batteries. In order to solve the above problems, the present application provides a modified current collector and a preparation method thereof, and a lithium-ion battery.
[0021] In a typical embodiment of the present application, a modified current collector is provided, which includes a first functional modified coating, a first nano-carbon coating, a current collector, a second nano-carbon coating and a second functional modified coating stacked in sequence; the first nano-carbon coating and the second nano-carbon coating each independently include a nano-carbon coating material; the first functional modified coating and the second functional modified coating each independently include a nano-carbon coating material and a functionalized modified material.
[0022] The modified current collector of the stacked structure of the present application, on the one hand, the first nano-carbon coating and the second nano-carbon coating can enhance the conductive network between the active material and the current collector; on the other hand, the nano-carbon coating material and the functionalized modified material in the first functional modified coating and the second functional modified coating are compounded to increase the porosity, thereby further improving the Li + The diffusion rate in the electrode increases the Li + The transmission capacity of ions, and the electron diffusion channel formed from the first nanocarbon coating to the first functional modified coating (or from the second nanocarbon coating to the second functional modified coating) is designed with an increasing gradient, thereby improving the interface contact impedance and the bonding strength, thereby alleviating the performance degradation caused by the interface stress during the long cycle. Through the synergistic effect of the above two aspects, it is possible to enhance the conductive network between the active material and the current collector, and at the same time increase the ion transmission capacity, thereby reducing the polarization internal resistance and inhibiting the growth of the DCR of the lithium-ion battery during the charge and discharge cycle, thereby improving the rate performance and cycle life of the lithium-ion battery. In addition, the modified current collector having the above structure has abundant porosity, which helps to improve its wettability in the electrolyte.
[0023] In one embodiment of the present application, the bending factor ratio of the modified current collector is in, is the bending factor of the first nano-carbon coating or the second nano-carbon coating, is the bending factor of the first functional modified coating or the second functional modified coating; the bending factor ratio of the modified current collector is 5 to 90%, preferably 10 to 80%; and / or the electronic conductivity ratio of the modified current collector is Among them, δ C is the electronic conductivity of the first nanocarbon coating or the second nanocarbon coating, δ Fis the electronic conductivity of the first functional modified coating or the second functional modified coating; the electronic conductivity ratio of the modified current collector is 2 to 85%, preferably 5 to 80%.
[0024] It is preferred to control the bending factor ratio of the modified current collector within the above range, which is conducive to giving full play to the synergistic effect between the first nano-carbon coating and the first functional modified coating (or the second nano-carbon coating and the second functional modified coating). Thus, the modified current collector maintains good electrical conductivity even in a bent or deformed state; controlling the electronic conductivity ratio of the modified current collector within the above range is conducive to effectively transmitting current and weakening the internal polarization of the battery, thereby helping to improve the rate performance and cycle life of the lithium-ion battery.
[0025] In one embodiment of the present application, the mass content of the functionalized modified material in the first functionally modified coating is 0.05-50%; and / or, the mass content of the functionalized modified material in the second functionally modified coating is 0.05-50%; and / or, the nanocarbon coating material is selected from any one or more of conductive graphite, carbon black, graphene, carbon nanotubes and VGCF; and / or, the functionalized modified material is selected from any one or more of transition metal oxide nanowires, transition metal oxide nanofibers, conductive polymer nanowires, conductive polymer nanofibers, MXene and MOFs.
[0026] It is preferred to control the mass content of the functionalized modified material in the first functional modified coating and the mass content of the functionalized modified material in the second functional modified coating within the above range, which helps to increase the porosity of the first functional modified coating and the second functional modified coating, thereby helping to improve Li + The diffusion rate in the electrode. It is preferred that the types of nano-carbon coating materials and functional modified materials are within the above range, which helps the nano-carbon coating materials and functional modified materials to be more effectively composited, thereby helping to enhance the conductive network between the active material and the current collector and improve Li + The ion transport capability helps to improve the rate performance and cycle life of lithium-ion batteries.
[0027] In one embodiment of the present application, the transition metal oxide nanowires and transition metal oxide nanofibers are each independently selected from RuO 2 、MnO 2 、V 2 O 5 、NiO 2 and any one or more of their corresponding derivatives; and / or, the conductive polymer nanowires and the conductive polymer nanofibers are each independently selected from any one or more of polyaniline, polypyrrole, polythiophene and their corresponding derivatives; and / or, MXene is selected from the group consisting of: n+1 X n Tx Two-dimensional layered materials derived from transition metal carbides, with a general chemical formula of M n+1 X n T x The two-dimensional layered material derived from transition metal nitrides, with the general chemical formula M n+1 X n T x Any one or more of the two-dimensional layered materials derived from transition metal carbonitrides, wherein M is a transition metal element, and M is selected from any one or more of Ti, V, Cr, Zr and Nb; X is a carbon element and / or a nitrogen element, T x is a surface group, the surface group is selected from any one or more of hydroxyl, fluorine, and carbonyl, 1≤n≤4; and / or, MOFs is a porous material composed of metal and organic ligands, the metal is metal ions and / or metal clusters, and MOFs is selected from any one or more of reticular metal-organic framework materials (IRMOFs), zeolite imidazolate framework materials (ZIFs), Levasil framework materials (MILs) and pore-channel framework materials (PCNs).
[0028] Preferably, the types of transition metal oxide nanowires / fibers, conductive polymer nanowires / fibers, MXene and MOFs are within the above range, which helps to composite them with nanocarbon coating materials to form gradient-designed electron diffusion channels, thereby improving interface contact impedance, increasing bonding strength and alleviating performance degradation caused by interface stress during long cycles.
[0029] In one embodiment of the present application, the thickness of the first nano-carbon coating and the second nano-carbon coating is independently 0.5 to 80 μm; and / or, the width of the first nano-carbon coating and the second nano-carbon coating is independently 50 to 1000 mm; and / or, the thickness of the first functional modified coating and the second functional modified coating is independently 0.5 to 80 μm; and / or, the width of the first functional modified coating and the second functional modified coating is independently 50 to 1000 mm; and / or, the first functional modified coating, The thickness ratio of the first nano-carbon coating and the current collector is 10-60:10-60:10-15; and / or, the thickness ratio of the second functional modified coating, the second nano-carbon coating and the current collector is 10-60:10-60:10-15; and / or, the thickness of the current collector is 6-16 μm; the current collector is copper foil or aluminum foil; and / or, the thickness of the aluminum foil is 12-16 μm; and / or, the thickness of the copper foil is 6-12 μm; and / or, the porosity of the modified current collector is 20-80%, preferably 40-80%.
[0030] It is preferred to control the thickness of the first nano-carbon coating and the second nano-carbon coating and the thickness of the first functional modified coating and the second functional modified coating within the above range, which helps to reduce the polarization internal resistance and is more helpful to regulate Li+ Controlling the thickness ratio of the first functional modified coating, the first nanocarbon coating and the current collector within the above range helps to further improve Li + It is preferred to control the type of current collector, the thickness of aluminum foil and copper foil within the above range, which helps to maintain the conductivity and mechanical strength of the modified current collector, thereby helping to improve the cycle life of the lithium ion battery.
[0031] In another typical embodiment of the present application, a method for preparing the above-mentioned modified current collector is provided, and the preparation method comprises: step S1, mixing raw materials including nano-carbon coating material, a first dispersant, a first organic solvent and a first adhesive for a first time to obtain a nano-carbon coating slurry; step S2, mixing raw materials including nano-carbon coating material, a functional modified material, a second dispersant, a second organic solvent and a second adhesive for a second time to obtain a functional modified coating slurry; step S3, coating the nano-carbon coating slurry on two opposite surfaces of the current collector respectively to form a first nano-carbon coating and a second nano-carbon coating; step S4, coating the functional modified coating slurry on the surfaces of the first nano-carbon coating and the second nano-carbon coating away from the current collector respectively to form a first functional modified coating and a second functional modified coating to obtain a modified current collector.
[0032] The present invention combines the nano-carbon coating material and the functional modified material to obtain the first functional modified coating and the second functional modified coating, which can not only increase the porosity, but also improve the Li + The diffusion rate in the electrode can also reduce the polarization internal resistance. Through the coating method in step S3 and step S4, the modified current collector of the first functional modified coating, the first nano-carbon coating, the current collector, the second nano-carbon coating and the second functional modified coating arranged in the above stacked manner can be obtained, which can not only enhance the conductive network between the active material and the current collector, but also increase the ion transmission capacity at the same time, thereby reducing the polarization internal resistance and inhibiting the growth of the DCR of the lithium-ion battery during the charge and discharge cycle, thereby improving the rate performance and cycle life of the lithium-ion battery.
[0033] In one embodiment of the present application, the above step S1 also includes: step S11, performing a first dispersion of the nano-carbon coating material, the first dispersant and the first organic solvent to obtain a first conductive paste; step S12, performing a first mixing of the first conductive paste and the first adhesive to obtain a nano-carbon coating slurry; wherein the mass ratio of the nano-carbon coating material, the first dispersant and the first organic solvent is 1:0.01-0.5:2-50; and / or, the viscosity of the nano-carbon coating slurry is 800-10000 mPa·s, preferably 850-9000 mPa·s; and / or, the rotation speed of the first dispersion is 20-10000 rpm, and / or, The first dispersion time is 0.5 to 1.5 hours, and / or the first mixing time is 0.5 to 24 hours; and / or the first dispersant is selected from any one or more of anionic dispersants, cationic dispersants, nonionic dispersants and electrically neutral dispersants; and / or the first organic solvent is selected from any one or more of N-methylpyrrolidone (NMP), γ-butyrolactone (GBL), dimethylformamide (DMF); and / or the first adhesive is selected from any one or more of polyvinylidene fluoride (PVDF), styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC), polyacrylic acid (PAA), and polyacrylonitrile (PAN).
[0034] It is preferred to control the mass ratio of the nano-carbon coating material, the first dispersant and the first organic solvent, the speed and time of the first dispersion, and the types of the first dispersant and the first organic solvent within the above range, which helps the nano-carbon coating material to be better dispersed in the first organic solvent, thereby obtaining the first conductive slurry. It is preferred to control the first mixing time and the type of the first adhesive within the above range, which helps to obtain a nano-carbon coating slurry with a viscosity within the above range, thereby facilitating coating on the current collector. It is preferred that the anionic dispersant is sodium acetate or sodium benzenesulfonate, the cationic dispersant is polyethyleneimine, and the non-ionic dispersant is polyvinyl pyrrolidone or polyethylene glycol, which helps to improve the dispersibility of the nano-carbon coating material.
[0035] In one embodiment of the present application, the above-mentioned step S2 also includes: step S21, performing a second dispersion of the nano-carbon coating material, the functional modified material, the second dispersant and the second organic solvent to obtain a second conductive paste; and step S22, performing a second mixing of the second conductive paste and the second adhesive to obtain a functional modified coating slurry; wherein the mass ratio of the nano-carbon coating material, the functional modified material, the second dispersant and the second organic solvent is 1: 0.01-0.95: 0.01-0.5: 2-50; and / or the viscosity of the functional modified coating slurry is 1200-10000 mPa·s, preferably 1500-9 500mPa·s; and / or, the rotation speed of the second dispersion is 50 to 8000rpm, and / or, the time of the second dispersion is 0.5 to 1.5h, and / or, the time of the second mixing is 0.5 to 24h; and / or, the second dispersant is selected from any one or more of anionic powders, cationic dispersants, non-ionic dispersants and electrically neutral dispersants; and / or, the second organic solvent is selected from any one or more of N-methylpyrrolidone, γ-butyrolactone, and dimethylformamide; and / or, the second adhesive is selected from any one or more of polyvinylidene fluoride, styrene-butadiene rubber, carboxymethyl cellulose, polyacrylic acid, and polyacrylonitrile.
[0036] It is preferred to control the mass ratio of the nano-carbon coating material, the functional modified material, the second dispersant and the second organic solvent, the rotation speed and time of the second dispersion, and the type of the second dispersant and the second organic solvent within the above range, which not only helps the nano-carbon coating material and the functional modified material to be better dispersed in the second organic solvent, but also helps the nano-carbon coating material and the functional modified material to be better composited, thereby obtaining a second conductive slurry. It is preferred to control the second mixing time and the type of the second adhesive within the above range, which helps to obtain a functional modified coating slurry with a viscosity within the above range, thereby helping to coat the first nano-carbon coating and the second nano-carbon coating to obtain a modified current collector.
[0037] In one embodiment of the present application, the above-mentioned step S3 also includes cleaning the current collector before coating, and the cleaning agent used for the cleaning treatment is an acid solution, and the acid solution is selected from any one or more of 0.5-50wt% acetic acid solution, 0.5-37wt% hydrochloric acid solution and 0.5-45wt% phosphoric acid solution; and / or the pH value of the acid solution is 1-6.
[0038] Preferably, the above-mentioned acid solution is used as a cleaning agent to clean the surface current collector, which helps to more fully remove surface impurities of the current collector, thereby helping to ensure the quality of subsequent coating.
[0039] In another typical embodiment of the present application, a lithium-ion battery is provided, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet and the negative electrode sheet each independently comprise the above-mentioned modified current collector.
[0040] The lithium ion battery using the modified current collector has higher rate performance and cycle life.
[0041] The beneficial effects of the present application will be further illustrated below in conjunction with embodiments.
[0042] Example 1
[0043] Conductive graphite, a nano-carbon coating material, polyethyleneimine, a first dispersant, and DMF, a first organic solvent, are first dispersed in a mass ratio of 1:0.01:2 to obtain a first conductive slurry, wherein the first dispersion speed is 20 rpm and the first dispersion time is 0.5 h; the first conductive slurry and the first adhesive PVDF are first mixed to obtain a nano-carbon coating slurry with a viscosity of 800 mPa·s, and the first mixing time is 0.5 h;
[0044] The conductive graphite of nanocarbon coating material and the functional modified material RuO 2 , the second dispersant polyethyleneimine and the second organic solvent DMF are dispersed for the second time in a mass ratio of 1:0.01:0.01:2 to obtain a second conductive slurry, wherein the second dispersion rotation speed is 50 rpm and the second dispersion time is 0.5 h; the second conductive slurry and the second adhesive PVDF are mixed for a second time, and the second mixing time is 0.5 h to obtain a functional modified coating slurry with a viscosity of 1200 mPa·s.
[0045] Before coating, a copper foil current collector with a thickness of 6 μm and a weight of 1.5 g is cleaned with a 50 wt% acetic acid solution to remove surface impurities, wherein the pH value of the acetic acid solution is 1, and nano-carbon coating slurry is coated on both sides of the copper foil current collector to form a first nano-carbon coating and a second nano-carbon coating, wherein the first nano-carbon coating has a thickness of 0.5 μm and a width of 50 mm, and the second nano-carbon coating has a thickness of 0.5 μm and a width of 50 mm; functional modified coating slurry is coated on the surfaces of the first nano-carbon coating and the second nano-carbon coating away from the copper foil current collector to form a first functional modified coating and a second functional modified coating, wherein the first functional modified coating has a thickness of 0.5 μm and a width of 50 mm, and the second functional modified coating has a thickness of 0.5 μm and a width of 50 mm, to obtain a modified current collector, the structure of which is as follows: Figure 1 shown.
[0046] Example 2
[0047] Conductive graphite, a nano-carbon coating material, polyethyleneimine, a first dispersant, and NMP, a first organic solvent, are first dispersed in a mass ratio of 1:0.2:30 to obtain a first conductive slurry, wherein the first dispersion speed is 5000 rpm and the first dispersion time is 1 hour; the first conductive slurry and the first adhesive SBR are first mixed to obtain a nano-carbon coating slurry with a viscosity of 5000 mPa·s, and the first mixing time is 12 hours;
[0048] The nanocarbon coating material carbon black, the functional modified material polyaniline, the second dispersant polyethyleneimine and the second organic solvent NMP are dispersed for the second time in a mass ratio of 1:0.5:0.3:25 to obtain a second conductive slurry, wherein the second dispersion rotation speed is 4000 rpm and the second dispersion time is 1 hour; the second conductive slurry and the second adhesive SBR are mixed for a second time, and the second mixing time is 12 hours to obtain a functional modified coating slurry with a viscosity of 4500 mPa·s.
[0049] Before coating, a copper foil current collector with a thickness of 9 μm and a weight of 3 g is cleaned with a 25 wt% acetic acid solution to remove surface impurities, wherein the pH value of the acetic acid solution is 3, and nano-carbon coating slurry is coated on both sides of the copper foil current collector to form a first nano-carbon coating and a second nano-carbon coating, wherein the first nano-carbon coating has a thickness of 50 μm and a width of 300 mm, and the second nano-carbon coating has a thickness of 50 μm and a width of 300 mm; functional modified coating slurry is coated on the surfaces of the first nano-carbon coating and the second nano-carbon coating away from the copper foil current collector to form a first functional modified coating and a second functional modified coating, wherein the first functional modified coating has a thickness of 50 μm and a width of 300 mm, and the second functional modified coating has a thickness of 50 μm and a width of 300 mm, to obtain a modified current collector, the structure of which is as follows: Figure 1 shown.
[0050] Example 3
[0051] The nano-carbon coating material graphene, the first dispersant polyethyleneimine and the first organic solvent GBL are first dispersed in a mass ratio of 1:0.5:50 to obtain a first conductive slurry, wherein the first dispersion speed is 9000 rpm and the first dispersion time is 1.5 hours; the first conductive slurry and the first adhesive PAN are first mixed to obtain a nano-carbon coating slurry with a viscosity of 10000 mPa·s, and the first mixing time is 24 hours;
[0052] The nano-carbon coating material carbon nanotubes, the functional modified material zeolite imidazole ester framework material, the second dispersant polyethyleneimine and the second organic solvent GBL are dispersed for the second time in a mass ratio of 1:0.95:0.5:50 to obtain a second conductive slurry, wherein the second dispersion rotation speed is 8000 rpm and the second dispersion time is 1.5 h; the second conductive slurry and the second adhesive PAN are mixed for the second time, and the first mixing time is 24 h to obtain a functional modified coating slurry with a viscosity of 10000 mPa·s.
[0053] Before coating, a copper foil current collector with a thickness of 9 μm and a weight of 3 g is cleaned with a 0.5 wt% acetic acid solution to remove surface impurities, wherein the pH value of the acetic acid solution is 6, and nano-carbon coating slurry is coated on both sides of the copper foil current collector to form a first nano-carbon coating and a second nano-carbon coating, wherein the first nano-carbon coating has a thickness of 80 μm and a width of 1000 mm, and the second nano-carbon coating has a thickness of 80 μm and a width of 1000 mm; functional modified coating slurry is coated on the surfaces of the first nano-carbon coating and the second nano-carbon coating away from the copper foil current collector to form a first functional modified coating and a second functional modified coating, wherein the first functional modified coating has a thickness of 80 μm and a width of 1000 mm, and the second functional modified coating has a thickness of 80 μm and a width of 1000 mm, to obtain a modified current collector, the structure of which is as follows: Figure 1 shown.
[0054] Example 4
[0055] The difference from Example 1 is that the bending factor ratio of the modified current collector is 5%.
[0056] Example 5
[0057] The difference from Example 1 is that the bending factor ratio of the modified current collector is 90%.
[0058] Example 6
[0059] The difference from Example 1 is that the bending factor ratio of the modified current collector is 95%.
[0060] Example 7
[0061] The difference from Example 1 is that the electronic conductivity ratio of the modified current collector is 2%.
[0062] Example 8
[0063] The difference from Example 1 is that the electronic conductivity ratio of the modified current collector is 85%.
[0064] Example 9
[0065] The difference from Example 1 is that the electronic conductivity ratio of the modified current collector is 90%.
[0066] Example 10
[0067] The difference from Example 1 is that the mass content of the functional modified material in the first functional modified coating is 0.05%, and the mass content of the functional modified material in the second functional modified coating is 0.05%, and finally a modified current collector is obtained.
[0068] Embodiment 11
[0069] The difference from Example 1 is that the mass content of the functional modified material in the first functional modified coating is 50%, and the mass content of the functional modified material in the second functional modified coating is 50%, and finally a modified current collector is obtained.
[0070] Example 12
[0071] The difference from Example 1 is that the mass content of the functional modified material in the first functional modified coating is 60%, and the mass content of the functional modified material in the second functional modified coating is 60%, and finally a modified current collector is obtained.
[0072] Embodiment 13
[0073] The difference from Example 1 is that the thickness ratio of the first functional modified coating, the first nano-carbon coating and the current collector in the modified current collector is 60:60:15.
[0074] Embodiment 14
[0075] The difference from Example 1 is that the thickness ratio of the first functional modified coating, the first nano-carbon coating and the current collector in the modified current collector is 60:60:16.
[0076] Embodiment 15
[0077] The difference from Example 1 is that the mass ratio of the nano-carbon coating material conductive graphite, the first dispersant polyethyleneimine and the first organic solvent DMF is 1:0.5:50, and finally a modified current collector is obtained.
[0078] Example 16
[0079] The difference from Example 1 is that the mass ratio of the nano-carbon coating material conductive graphite, the first dispersant polyethyleneimine and the first organic solvent DMF is 1:1:50, and finally a modified current collector is obtained.
[0080] Embodiment 17
[0081] The difference from Example 1 is that the conductive graphite of the nano-carbon coating material and the functional modified material RuO 2The mass ratio of the second dispersant polyethyleneimine and the second organic solvent DMF is 1:0.95:0.5:50, and finally a modified current collector is obtained.
[0082] Embodiment 18
[0083] The difference from Example 1 is that the conductive graphite of the nano-carbon coating material and the functional modified material RuO 2 , the mass ratio of the second dispersant polyethyleneimine and the second organic solvent DMF is 1:1:1:50, and finally a modified current collector is obtained.
[0084] Embodiment 19
[0085] The difference from Example 1 is that the rotation speed of the first dispersion is 10000 rpm, the time of the first dispersion is 1.5 h, the rotation speed of the second dispersion is 8000 rpm, the time of the second dispersion is 1.5 h, and finally a modified current collector is obtained.
[0086] Embodiment 20
[0087] The difference from Example 1 is that the rotation speed of the first dispersion is 11000 rpm, the time of the first dispersion is 1.5 h, the rotation speed of the second dispersion is 9000 rpm, the time of the second dispersion is 1.5 h, and finally a modified current collector is obtained.
[0088] Comparative Example 1
[0089] The difference from Example 1 is that no coating is applied on both sides of the current collector, thereby obtaining a modified current collector.
[0090] Comparative Example 2
[0091] The difference from Example 1 is that the nano-carbon coating slurry is coated on both sides of the current collector respectively to form a first nano-carbon coating and a second nano-carbon coating to obtain a modified current collector.
[0092] Test Method
[0093] Porosity testing method: The porosity is determined by nitrogen adsorption method, and the isotherms from low pressure (0.00001 Torr) to saturation pressure (760 Torr) are recorded. The condensed gas volume of the sample under different pressure conditions is measured, and its isothermal adsorption and desorption curves are plotted to obtain its pore volume and pore size distribution curves for analysis and calculation of the porosity.
[0094] The test method of DCR growth rate is as follows: the test battery is charged to 3.70V at 0.33C constant current and constant voltage, cut off at 0.05C, then discharged at 0.33C for 90min, left for 10min, and the terminal voltage V1 is recorded; then discharged at 2C (current I) for 10s, the terminal voltage V2 is recorded, and the DC impedance of the battery is calculated according to the following formula: DC impedance = |V1-V2| / I.
[0095] Testing method for bending factor ratio: in, is the bending factor of the first nano-carbon coating or the second nano-carbon coating, The bending factor of the first functional modified coating or the second functional modified coating. The test method of the bending factor of the above coating is as follows: the sample is reconstructed into 3D imaging using a focused ion beam scanning electron microscope (FIB-SEM), and the bending factor of the three-dimensional structure is calculated using a geometric method. First, all the starting plane phases are marked with a unit distance, and then the effective distance of adjacent voxels is marked and the effective length of the channel is repeatedly measured through a phase network. The square of the ratio of the effective length to the actual length of the sample is calculated, which is the above coating bending factor.
[0096] Electronic conductivity ratio: Among them, δ C is the electronic conductivity of the first nanocarbon coating or the second nanocarbon coating, δ F The electronic conductivity of the first functional modified coating or the second functional modified coating. The test method of the electronic conductivity of the above coating is as follows: the electronic conductivity of the coating is calculated by the four-probe method, the resistance R of the conductor is calculated by measuring the current passing through the conductor and the voltage drop through the conductor, and the length and cross-sectional area ratio K of the sample to be tested are measured, K*(1 / R), which is the electronic conductivity of the above coating.
[0097] Applying the modified current collector to LiFePO 4 / Graphite system soft-pack battery cells undergo 1000 cycles of high temperature cycling.
[0098] The modified current collectors in the above embodiments and comparative examples were subjected to performance tests, and the test results are shown in Table 1.
[0099] Table 1
[0100]
[0101]
[0102] in, Figure 1 is a schematic diagram of the structure of the modified current collector of the present application, from Figure 1It can be seen that the modified current collector includes a first functional modified coating 1, a first nanocarbon coating 2, a current collector 3, a second nanocarbon coating 4 and a second functional modified coating 5 which are stacked in sequence; the first nanocarbon coating 1 and the second nanocarbon coating 2 each independently include a nanocarbon coating material 6; the first functional modified coating 4 and the second functional modified coating 5 each independently include a nanocarbon coating material 6 and a functional modified material, and the functional modified material may include transition metal oxide nanowires and transition metal oxide nanofibers 7, conductive polymer nanowires and conductive polymer nanofibers 8, MXene 9, and MOFs 10.
[0103] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0104] The modified current collector of the stacked structure of the present application, on the one hand, the first nano-carbon coating and the second nano-carbon coating can enhance the conductive network between the active material and the current collector; on the other hand, the nano-carbon coating material and the functionalized modified material in the first functional modified coating and the second functional modified coating are compounded to increase the porosity, thereby further improving the Li + The diffusion rate in the electrode increases the Li + The transmission capacity of ions, and the electron diffusion channel formed from the first nanocarbon coating to the first functional modified coating (or from the second nanocarbon coating to the second functional modified coating) is designed with an increasing gradient, thereby improving the interface contact impedance and the bonding strength, thereby alleviating the performance degradation caused by the interface stress during the long cycle. Through the synergistic effect of the above two aspects, it is possible to enhance the conductive network between the active material and the current collector, and at the same time increase the ion transmission capacity, thereby reducing the polarization internal resistance and inhibiting the growth of the DCR of the lithium-ion battery during the charge and discharge cycle, thereby improving the rate performance and cycle life of the lithium-ion battery. In addition, the modified current collector having the above structure has abundant porosity, which helps to improve its wettability in the electrolyte.
[0105] The above are only embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A modified current collector, characterized in that: The modified current collector comprises a first functional modified coating, a first nano-carbon coating, a current collector, a second nano-carbon coating and a second functional modified coating which are sequentially stacked; The first nano-carbon coating layer and the second nano-carbon coating layer each independently comprise a nano-carbon coating material; The first functional modified coating and the second functional modified coating each independently comprise a nano-carbon coating material and a functional modified material.
2. The modified current collector according to claim 1, characterized in that: The bending factor ratio of the modified current collector is in, is the bending factor of the first nano-carbon coating or the second nano-carbon coating, is the bending factor of the first functional modified coating or the second functional modified coating; The bending factor ratio of the modified current collector is 5 to 90%, preferably 10 to 80%; And / or, the electronic conductivity ratio of the modified current collector is Among them, δ C is the electronic conductivity of the first nano-carbon coating or the second nano-carbon coating, δ F is the electronic conductivity of the first functional modified coating or the second functional modified coating; The electronic conductivity ratio of the modified current collector is 2 to 85%, preferably 5 to 80%.
3. The modified current collector according to claim 1 or 2, characterized in that: The mass content of the functionalized modified material in the first functional modified coating is 0.05 to 50%; and / or, the mass content of the functionalized modified material in the second functional modified coating is 0.05 to 50%; and / or, the nanocarbon coating material is selected from any one or more of conductive graphite, carbon black, graphene, carbon nanotubes and VGCF; and / or, the functionalized modified material is selected from any one or more of transition metal oxide nanowires, transition metal oxide nanofibers, conductive polymer nanowires, conductive polymer nanofibers, MXene and MOFs.
4. The modified current collector according to claim 3, characterized in that: The transition metal oxide nanowires and the transition metal oxide nanofibers are each independently selected from any one or more of RuO2, MnO2, V2O5, NiO2 and their corresponding derivatives; And / or, the conductive polymer nanowires and the conductive polymer nanofibers are independently selected from any one or more of polyaniline, polypyrrole, polythiophene and their corresponding derivatives; And / or, the MXene is selected from the group consisting of n+1 X n T x Two-dimensional layered materials derived from transition metal carbides, with a general chemical formula of M n+1 X n T x The two-dimensional layered material derived from transition metal nitrides, with the general chemical formula M n+1 X n T x Any one or more of the two-dimensional layered materials derived from transition metal carbonitrides, wherein M is a transition metal element, and M is selected from any one or more of Ti, V, Cr, Zr and Nb; X is a carbon element and / or a nitrogen element, T x is a surface group, wherein the surface group is selected from any one or more of a hydroxyl group, a fluoro group, and a carbonyl group, and 1≤n≤4; And / or, the MOFs are porous materials composed of metals and organic ligands, the metals are metal ions and / or metal clusters, and the MOFs are selected from any one or more of mesh metal-organic framework materials, zeolite imidazolate framework materials, Levasil framework materials and pore-channel framework materials.
5. The modified current collector according to any one of claims 1 to 4, characterized in that: The thickness of the first nano-carbon coating and the second nano-carbon coating is independently 0.5 to 80 μm; and / or, the width of the first nano-carbon coating and the second nano-carbon coating is independently 50 to 1000 mm; and / or, the thickness of the first functional modified coating and the second functional modified coating is independently 0.5 to 80 μm; and / or, the width of the first functional modified coating and the second functional modified coating is independently 50 to 1000 mm; and / or, the thickness ratio of the first functional modified coating, the first nano-carbon coating and the current collector is 10-60:10-60:10-15; and / or, the thickness ratio of the second functional modified coating, the second nano-carbon coating and the current collector is 10-60:10-60:10-15; And / or, the thickness of the current collector is 6 to 16 μm; The current collector is copper foil or aluminum foil; and / or the thickness of the aluminum foil is 12 to 16 μm; and / or the thickness of the copper foil is 6 to 12 μm; and / or the porosity of the modified current collector is 20 to 80%, preferably 40 to 80%.
6. A method for preparing the modified current collector according to any one of claims 1 to 5, characterized in that: The preparation method comprises: Step S1, mixing raw materials including a nano-carbon coating material, a first dispersant, a first organic solvent and a first adhesive to obtain a nano-carbon coating slurry; Step S2, performing a second mixing of raw materials including the nano-carbon coating material, the functional modified material, the second dispersant, the second organic solvent and the second adhesive to obtain a functional modified coating slurry; Step S3, coating the nano-carbon coating slurry on two opposite surfaces of the current collector respectively to form a first nano-carbon coating and a second nano-carbon coating; Step S4, coating the functional modified coating slurry on the surfaces of the first nano-carbon coating and the second nano-carbon coating away from the current collector respectively to form a first functional modified coating and a second functional modified coating, that is, to obtain the modified current collector.
7. The preparation method according to claim 6, characterized in that: The step S1 further comprises: Step S11, performing a first dispersion on the nano-carbon coating material, the first dispersant and the first organic solvent to obtain a first conductive paste; Step S12, performing the first mixing of the first conductive slurry and the first adhesive to obtain the nano-carbon coating slurry; Wherein, the mass ratio of the nano-carbon coating material, the first dispersant and the first organic solvent is 1:0.01-0.5:2-50; and / or, the viscosity of the nano-carbon coating slurry is 800-10000 mPa·s, preferably 850-9000 mPa·s; and / or, the first dispersing speed is 20 to 10000 rpm, and / or, the first dispersing time is 0.5 to 1.5 h, and / or, the first mixing time is 0.5 to 24 h; And / or, the first dispersant is selected from any one or more of anionic dispersants, cationic dispersants, nonionic dispersants and electrically neutral dispersants; and / or, the first organic solvent is selected from any one or more of N-methylpyrrolidone, γ-butyrolactone, and dimethylformamide; And / or, the first adhesive is selected from any one or more of polyvinylidene fluoride, styrene-butadiene rubber, carboxymethyl cellulose, polyacrylic acid, and polyacrylonitrile.
8. The preparation method according to claim 6 or 7, characterized in that: The step S2 further comprises: Step S21, performing a second dispersion on the nano-carbon coating material, the functional modified material, the second dispersant and the second organic solvent to obtain a second conductive paste; Step S22, performing the second mixing of the second conductive paste and the second adhesive to obtain the functional modified coating paste; Wherein, the mass ratio of the nano-carbon coating material, the functional modified material, the second dispersant and the second organic solvent is 1: 0.01-0.95: 0.01-0.5: 2-50; and / or, the viscosity of the functional modified coating slurry is 1200-10000 mPa·s, preferably 1500-9500 mPa·s; and / or, the second dispersing speed is 50 to 8000 rpm, and / or, the second dispersing time is 0.5 to 1.5 h, and / or, the second mixing time is 0.5 to 24 h; And / or, the second dispersant is selected from any one or more of anionic dispersants, cationic dispersants, nonionic dispersants and electrically neutral dispersants; and / or, the second organic solvent is selected from any one or more of N-methylpyrrolidone, γ-butyrolactone, and dimethylformamide; And / or, the second adhesive is selected from any one or more of polyvinylidene fluoride, styrene-butadiene rubber, carboxymethyl cellulose, polyacrylic acid, and polyacrylonitrile.
9. The preparation method according to any one of claims 6 to 8, characterized in that: The step S3 also includes cleaning the current collector before the coating, wherein the cleaning agent used for the cleaning is an acid solution, and the acid solution is selected from any one or more of 0.5-50wt% acetic acid solution, 0.5-37wt% hydrochloric acid solution and 0.5-45wt% phosphoric acid solution; and / or the pH value of the acid solution is 1-6.
10. A lithium ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, characterized in that: The positive electrode sheet and / or the negative electrode sheet comprises the modified current collector according to any one of claims 1 to 5.
Citation Information
Patent Citations
Graphene composite negative current collector, preparation method thereof and lithium ion battery
CN103579632A
Current collector, preparation method of current collector and lithium ion battery comprising current collector
CN105375035A
Negative-electrode-free lithium metal battery, negative electrode current collector of negative electrode-free lithium metal battery and preparation method
CN113013417A
Negative current collector, preparation method thereof, negative pole piece with negative current collector, and lithium secondary battery
CN115842133A
Pole piece and secondary battery comprising same
CN115911246A
